Vitamin D regulates prostate cell metabolism via genomic and non-genomic mitochondrial redox-dependent mechanisms. Issue 195 (December 2019) - Blajszczak, Chuck C.; Nonn, Larisa
Highlights: Conversion of 25(OH)D –1, 25(OH)2D changes local redox balance in prostatic cells. CYP27B1 is important in the maintenance of prostatic mitochondrial function. Vitamin D impacts mitochondrial composition through transcriptional regulation. Abstract: Vitamin D deficiency has been associated with increased risk for aggressive prostate cancer (PCa). Prostate epithelium has a unique metabolism compared to other tissues. Normal prostate exhibits low levels of mitochondrial respiration and there is a metabolic switch to increased oxidative phosphorylation in PCa. 25-hydroxyvitamin D (25(OH)D) is the major circulating form of vitamin D and is used clinically to determine vitamin D status. Activation of 25(OH)D to the transcriptionally active form, 1, 25(OH)2 D occurs via a reduction-oxidation (redox) reaction within the mitochondria that is catalyzed by the P450 enzyme, CYP27B1. We sought to determine if hydroxylation of 25(OH)D by CYP27B1 contributes to non-genomic activity of vitamin D by altering the redox-dependent state of the mitochondria in benign prostate epithelial cells. Exposure to 25(OH)D produced a transient pro-oxidant effect and change in mitochondrial membrane potential that was dependent on CYP27B1. Extended exposure ultimately suppressed mitochondrial respiration, consistent with a protective effect of 25(OH)D in supporting benign prostate metabolism. To model physiologically relevant changes in vitamin D, cells were cultured in constant 25(OH)D then changed to high or deficient concentrations. This model also incurred a biphasic effect with a pro-oxidant shift after short exposure followed by decreased respiration after 16 h. Several genes involved in redox cycling and Mitochondrial Health were regulated by 25(OH)D in these cells. These results indicate a secondary non-genomic mechanism for vitamin D to contribute to prostate cell health by supporting normal mitochondrial respiration.